Unraveling business model innovation in firm internationalization: A systematic literature review and future research agenda - Evers, Natasha; Ojala, Arto; Sousa, Carlos M. P.; Criado-Rialp, Alex (Elsevier, 2023)
The international business literature has witnessed a rapid growth of studies examining business model innovation (BMI) in firm internationalization, particularly over the last decade. Despite this increased line of inquiry, the body of knowledge on BMI and firm internationalization remains largely fragmented and unsynthesized, thus compromising theoretical and empirical advancements in the field. Although past reviews have multiplied on BMI in the mainstream business literature, none have been conducted in the context of international business. The primary goal of this review is to synthesize and evaluate the research on BMI in international business and to propose a future research agenda. Accordingly, we take stock of the literature and critically assess and examine 70 peer-reviewed articles published between 1996 and 2021. This study contributes to the extant literature by capturing the current body of knowledge on this topic and further advances and cultivates the dialogue between BMI and international business. We provide greater clarification of the BMI construct by proposing more fine-grained BMI constructs to be used to advance theory and empirical testing in future IB research. We finally contribute to the literature by mapping out a future research agenda supported by an integrative framework to advance research at the interface of BMI and firm internationalization.
Keywords: Business model; Business model innovation; Internationalization; Systematic literature review; fi=Kansainvälinen liiketoiminta|en=International Business|